О новых методологических подходах к исследованию института гендера - Лавриненко, Н. (Социология: теория, методы, маркетинг, 2006)
The article’s theoretical conception proves that gender as a social phenomenon is wider and more complicated that merely the “gender order” notion, because gender is a social institution. The author analyzes the following components of the social institution of gender: gender statuses, gendered division of labor, gendered kinship, gendered biological (sexual) scripts, gendered characteristics of personality, gendered social control, gender ideology, and gender imagery. General discussions on gender components are reinforced with the data of sociological research on gender problems conducted in Ukraine. As a possible methodological approach for the study of gender institution may be used the theory of the social construction of gender developed by feministic researchers.